Sittig's handbook of toxic and hazardous chemicals and carcinogens - Pohanish, Richard P.; Sittig, Marshall (William Andrew, 2008)
For more than a quarter century, Sittig's Handbook of Toxic and Hazardous Chemicals and Carcinogens has proven to be among the most reliable, easy-to-use and essential reference works on hazardous materials. Sittig's 5th Edition remains the lone comprehensive work providing a vast array of critical information on the 2,100 most heavily used, transported, and regulated chemical substances of both occupational and environmental concern. Information is the most vital resource anyone can have when dealing with potential hazardous substance accidents or acts of terror. Sittig's provides extensive.